Larval Gnathostoma spinigerum Detected in Asian Swamp Eels, Monopterus albus, Purchased from a Local Market in Yangon, Myanmar - Chai, Jong-Yil (Korean J Parasitol, 2015)
The present study was performed to determine the infection status of swamp eels with Gnathostoma sp. larvae in Myanmar. We purchased total 37 Asian swamp eels, Monopterus albus, from a local market in Yangon in June and December 2013 and 2014. All collected eels were transferred with ice to our laboratory and each of them was examined by the artificial digestion technique. A total of 401 larval gnathostomes (1-96 larvae/eel) were detected in 33 (89.2%) swamp eels. Most of the larvae (n=383; 95.5%) were found in the muscle. The remaining 18 larvae were detected in the viscera. The advanced third-stage larvae (AdL(3)) were 2.3-4.4 mm long and 0.25-0.425 mm wide. The characteristic head bulb (0.093 × 0.221 mm in average size) with 4 rows of hooklets, muscular long esophagus (1.025 mm), and 2 pairs of cervical sacs (0.574 mm) were observed by light microscopy. The average number of hooklets in the 1st, 2nd, 3rd, and 4th rows was 41, 45, 48, and 51, respectively. As scanning electron microscopic findings, the characteristic 4-5 rows of hooklets on the head bulb, a cervical papilla, tegumental spines regularly arranged in the transverse striations, and an anus were well observed. Based on these morphological characters, they were identified as the AdL(3) of Gnathostoma spinigerum. By the present study, it has been confirmed for the first time that Asian swamp eels, M. albus, from Yangon, Myanmar are heavily infected with G. spinigerum larvae.